2010
DOI: 10.1007/s11741-010-0673-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue tests of composite beam by steel fiber reinforced self-stressing concrete in the hogging bending

Abstract: Through the experiments of 7 T-section composite beams, steel fiber reinforced self-stressing concrete (SFRSC) as the composite beam in the composite layer was studied under the hogging bending. The tests simulated composite layer tensile strain under the hogging bending of inverted loading composite beams, giving the relationship under the different fatigue stress ratios between fatigue cycles and steel bar's stress range, crack width, stiffness loss and damage, etc., in composite layer. This article establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In this case, reinforcement can be avoided except in some discontinuity or load introduction points. Hu et al [16], and Lin et al [17] have investigated the use of SFRC for the slabs of conventional composite beams to enhance its capacity in the hogging moment region. Cui, Nakashima et al [18,19] investigated diff erent layouts of shear connectors and applied them to a specifi c moment-resisting connection.…”
Section: Stress-strain Constitutive Law For Sfrcmentioning
confidence: 99%
“…In this case, reinforcement can be avoided except in some discontinuity or load introduction points. Hu et al [16], and Lin et al [17] have investigated the use of SFRC for the slabs of conventional composite beams to enhance its capacity in the hogging moment region. Cui, Nakashima et al [18,19] investigated diff erent layouts of shear connectors and applied them to a specifi c moment-resisting connection.…”
Section: Stress-strain Constitutive Law For Sfrcmentioning
confidence: 99%
“…6 Debonding damage may occur at the interface under external load, leading to the mutation of the cross-section's neutral axis and causing the entire structure's damage to abrupt change. [7][8][9] Existing studies have shown that the interfacial performance of the PC beams could greatly affect the mechanical performance of the component. [10][11][12] For the new-old concrete interface, the interfacial roughness and shear key have been proven to be the main parameters affecting the interface strength.…”
Section: Introductionmentioning
confidence: 99%
“…The interface between the pre‐cast and cast‐in‐place layers may become a weak part of the formed composite structure due to the local change of water‐cement ratio, concrete shrinkage, aggregates touching the surface of the pre‐cast layer, and improper concrete vibrating 6 . Debonding damage may occur at the interface under external load, leading to the mutation of the cross‐section's neutral axis and causing the entire structure's damage to abrupt change 7–9 . Existing studies have shown that the interfacial performance of the PC beams could greatly affect the mechanical performance of the component 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, many scholars have conducted some researches and put forward some feasible calculation theories and methods, such as energy-variational method, the finite plate strip method, the finite element method, and so on [1][2][3]. Some researchers have performed corresponding model experimental research [4][5][6][7]. Kristek solved the problem by using the method of series [8], independent of the condition of relative slip.…”
Section: Introductionmentioning
confidence: 99%